Unveiling single-particle composition, size, shape, and mixing state of freshly emitted Icelandic dust via electron microscopy analysis - Panta, Agnesh; Kandler, Konrad; Schepanski, Kerstin; Alastuey, Andres; Dagsson Waldhauserova, Pavla; Dupont, Sylvain; Eknayan, Melanie; González-Flórez, Cristina; González-Romero, Adolfo; Klose, Martina; Montag, Mara; Querol, Xavier; et al. (Atmospheric chemistry and physics, 2025)
Iceland is a significant high-latitude dust source area. Airborne Icelandic dust influences the climate system by interacting with radiation, clouds, and biogeochemical cycles; it also affects snow and ice albedo and air quality. These impacts are sensitive to the dust’s mineralogical, chemical, and physical properties. However, comprehensive measurements and analyses of Icelandic dust particles remain limited. This study examines dust samples collected during a field campaign in the Dyngjusandur desert (August–September 2021) using active and passive aerosol sampling. Over 190 000 individual particles, ranging from 0.1 to 120 µm, were analyzed for their chemical and physical properties using computer-controlled scanning electron microscopy/energy-dispersive X-ray spectroscopy (ccSEM/EDX). Results show heterogeneity in particle size, shape, and composition. The most abundant particle type was medium-Al mixed particles, likely glass-like, comprising 35 %–92 % of the aerosol volume. Sulfate particles, suggesting volcanic contributions, were detected in some samples. Iron (Fe)- and titanium (Ti)-rich particles made up 3.3 % and 6 % of the aerosol volume, respectively, mainly in the size fraction < 1 µm. The median aspect ratio ranged from 1.37 to 1.53, increasing with particle size. Our findings highlight key differences in Icelandic dust compared to Saharan dust, including higher iron and titanium content and a lack of potassium in Icelandic dust. Additionally, Icelandic dust shows a size-dependent increase in aspect ratio, unlike Saharan dust, which remains constant. These observations can improve model simulations that account for the effect of high-latitude dust in the Earth system.